Genome-wide association study of elite spring bread wheat (triticum aestivum l.) genotypes under drought conditions across different locations - Ed-Daoudy, Lamyae; Zakaria, EL Gataa; Sbabou, Laila; Tadesse, Wuletaw (2024)
Drought, is the main abiotic stressor that significantly reduces bread wheat's grain yield and related-traits. A genome-wide association study was conducted using the 10K wheat SNP markers for grain yield and related traits of 246 spring bread wheat genotypes from ICARDA to identify the genomic regions and marker-trait associations (MTAs) responsible for drought tolerance. Grain yield (GY), days to heading (DHE), days to maturity (DMA), plant height (PLH), and thousand kernel weight (TKW), were evaluated at Merchouch sta tion (Morocco); in the other hand only grain yield that was considered for the rest of the environments; Terbol (Lebanon), Kheferdan (Sudan), and ARC (Egypt), as well as Tassaout, and Sidi El Aidi (Morocco); spanning two years 2015-2016 and 2016-2017, as per variance analysis. Grain yield and related-traits showed a considerable variation among geno types. Moreover, GWAS using a mixed linear model (MLM), revealed 53 MTAs across the six environments on 14 chromosomes. With an average r 2 value of 0.26, Genome D has the highest linkage, followed by Genomes B and A with r2 values of 0.22 and 0.21, respectively. GY had the highest MTA rating (35), followed by TKW (9) and 3 for each of the other agronomic traits (DHE, DMA, PLH) at Merchouch station. “CAP8_c1393_327” was the most significant associated marker correlated with grain yield located on chromosome 3A across Sid El Aidi station. Additionally, the SNP markers “wsnp_Ra_c26091_35652620” displayed extremely significant and stable MTA for TKW on chromosome 5B at Merchouch station. The markers and candidate genes reported throughout this study have the potential to be used in marker-assisted selection to enhance wheat genotypes in terms of yield and resistance to drought limitations.